Histomorphometry of the epididymal region of domestic quail (Coturnix coturnix) of the italian variety (Bioscience Journal, 2017)
Epididymal region of domestic adult quail of the italina variety was studied by morphometric analysis concerning to the proximal and distal efferent ductules and the epididymal duct. They formed the proper segmental epididymal region structure in domestic quail prior observed during the four seasons of the year in the Botucatu city/SP/Brazil (22°53'09''S, 48°26'42''W, 840m), with tropical altitude climate, average annual temperature of 20,7 degrees. Parameters such as the tubular diameter and the luminal diameter, structure of the lining epithelium and luminal content, of all tubules of the epididymal region, were analyzed referring each segmental tubular area disposed along the epididymal region. It was verified that the efferent ductules occupied the major proportional distribution inside the epididymal region and plus the epididymal duct presented striking quantitative and qualitative variations during the autumn and spring. These seasons respectively represented the quiescent and active phases of this quail annual testis cycle. During summer and winter some variations of the epididymal region morphology were verified. Morphological data obtained in winter and in summer respectively allow characterizing them as intermediary phases of the annual reproductive cycle. However, no remarkable change in the proximal efferent ducts and distal efferent ducts was observed in winter and summer, for the spring events, such as already described during the annual testicular cycle of domestic quail. So the epididymal region of the domestic quail of the Italian variety is a single organ, whose size varies in the autumn, with minor relative average, and in the other seasons in which this organ maintain its usual dimensions.